Impact of the Ownership Structure on the Financial Performance of Banks: Comparative Study between Conventional and Islamic Banks - Haddad, Achraf; Ammari, Anis El; Bouri, Abdelfattah (International Journal of Accounting & Finance Review, 2019)
According to the literature of corporate governance, ownership structure is advanced as a non-dissociable mechanism of control intended to follow the stakeholders and especially used by shareholders to monitor the conflicts of interest and the opportunistic behavior of managers. Several previous studies have focused on the impact of ownership structure on financial performance separately in conventional or in Islamic banks. However, the comparative studies between these two impacts are non-existent. In this research, we compared the impacts of this governance mechanism on the financial performance in the two types of banks by using the Ordinary Least Squares method. Data relating to financial performance and ownership structure of banks come from 16 countries. Two samples were collected: the first one included 63 conventional banks, whereas the second one integrated 63 Islamic banks whose data are available over the period (2010-2018). Panel results showed that partial effect of each determinant of ownership structure on each measure of financial performance varied from one banks’ type to another and from one performance measure to another. Besides, the reconciliation of similar models revealed many differences between the same impacts’ signs. Therefore, we concluded that in both banks’ types the ownership structure has a positive impact on the financial performance. While, the negative part of the same impact is less significant in Islamic banks.JEL Classification:  F33, G20, G21, G24, G30.